Software Process Improvement and Capability Determination 13th International Conference, SPICE 2013, Bremen, Germany, June 4-6, 2013. Proceedings - Woronowicz, Tanja; Rout, Terry; O$1 (BConnor, Rory V.s; Dorling, Alec.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the 13th International Conference on Software Process Improvement and Capability Determination, SPICE 2013, held in Bremen, Germany, in June 2013. The 21 revised full papers presented and 7 short papers were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on process quality; medical device software processes; design and use of process models; studies of software development; agile development; IT service management; assessment for diagnosis.
Process quality -- Medical device software processes -- Design and use of process models -- Studies of software development -- Agile development -- IT service management -- Assessment for diagnosis.
Keywords: Computer science; Software engineering; Information systems; Information Systems; Management information systems; Computer Science; Management of Computing and Information Systems; Software Engineering; Business Information Systems; Computer Appl. in Administrative Data Processing